A Subtitling Analysis Of Noun Phrase In The Journey 2 (2012) Movie - Jannah, Miftahul, Dra. Dwi Haryanti, M. Hum, Drs. Sigit Haryanto, M. Hum (2013)
This research is descriptive qualitative research. The objectives of the research are to identify the translation shift of noun phrase and to describe the shift pattern of noun phrase translation in The Journey 2 Movie subtitle. The data are noun phrases found in The Journey 2 Movie subtitle. The researcher uses documentation as the method of collecting the data. The result of the research is from 334 data, there are 136 data belong to translation shift of noun phrase. The researcher finds two types of translation shift, they are level shift and structure shift. Level shift of noun phrase is divided into five parts, the first is noun phrase that is translated into clause, the shift pattern which occurs in this translation is from phrase changes into clause. Secondly, noun phrase is translated into noun, the shift pattern is from phrase changes into word or noun. The third is noun phrase that is translated into adjective, the shift pattern in this translation is from phrase changes into word or adjective. The fourth is noun phrase is translated into verb, the shift pattern which occurs is from phrase into word or verb. And the last is noun phrase that is translated into adverb, its shift pattern is from phrase changes into word or adverb. Then structural shift contains three parts, noun phrase is translated into adjective phrase, noun phrase is translated into verb phrase and noun phrase is translated into prepositional phrase. The shift pattern of this third translation shift is from phrase changes into phrase.